9. SURVEY ON EMERGENCY TRAINING NEEDS OF MEDICAL STAFF IN SOME EMERGENCY UNITS IN THE CENTRAL AND CENTRAL HIGHLANDS REGIONS (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe the training needs in pre-hospital emergency care among healthcare personnel working in selected emergency units in the Central and Central Highlands regions of Vietnam.Subjects and methods: A cross-sectional study was conducted among 116 healthcare workers from various emergency units in the Central and Central Highlands regions. Data were collected using a self-administered questionnaire and analyzed using SPSS version 20.0.Results: Among healthcare workers, the most essential competency identified was the ability to assess and manage initial trauma, reported by 93.1%. For pre-hospital emergency technicians, airway management was considered the most critical skill to be trained (83.6%). A majority (87.1%) indicated that training programs should include both theoretical knowledge and practical skills. For non-healthcare personnel, the most needed training topics were cardiopulmonary resuscitation and basic first aid for injuries, accounting for 86.2%. Regarding teaching methods, 74.1% preferred hands-on practice, and 51.7% favored simulation-based training.Conclusion: There is a need to develop and implement additional training programs tailored for personnel working in emergency care.
Keywords: Training needs; pre-hospital emergency care; emergency personnel.